2019
DOI: 10.3390/antiox8060161
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Profile and Antioxidant Activity of Italian Monovarietal Extra Virgin Olive Oils

Abstract: In the last years, the interest in Italian monovarietal oils has increased due to their specific organoleptic qualities. Extra virgin olive oils (EVOOs) are rich in phenolic compounds, secondary metabolites well known and studied for their nutraceutical properties. However, among EVOOs, there is great variability in phenolic composition due to the origin, the production technique, and mainly, the genotype. The aim of this work was to evaluate the different phenolic profiles and the antioxidant activities of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 45 publications
6
41
0
Order By: Relevance
“…r μg/g oil (Tuck and Hayball, 2002). s μg/g oil (Negro et al, 2019). t μg/g oil (Lazzerini and Domenici, 2017).…”
Section: Data Analysis: Kinetic Parameter Analysis Of Phba Thermal Dementioning
confidence: 99%
“…r μg/g oil (Tuck and Hayball, 2002). s μg/g oil (Negro et al, 2019). t μg/g oil (Lazzerini and Domenici, 2017).…”
Section: Data Analysis: Kinetic Parameter Analysis Of Phba Thermal Dementioning
confidence: 99%
“…In the same studies, higher concentrations of apigenin were reported reaching concentrations to the 8.72 and 5.51 ± 0.69 mg/kg, respectively [ 27 , 61 ]. Differences in the concentration of both compounds in non-ivory cultivars growing in an identical climate/environment area in Italy also was reported with concentrations between 2.2 ± 0.5–16.7 ± 0.6 mg/kg for the luteolin and 0.2 ± 0.1–9.2 ± 0.3 mg/kg for the apigenin [ 62 ]. The ripening stage is another factor that affects the concentrations of these compounds, increasing the content of luteolin with the maturity index whereas apigenin does not show any definite trend.…”
Section: Resultsmentioning
confidence: 95%
“…The oxidation reactions and free radical production lead to some oxidative stress-related disorders such as diabetes, arthritis, urolithiasis and cancer. The activity of phenolic compounds against oxidative stress-related mechanism can have substantial therapeutic applications in the pharmaceutical and nutraceutical industry 12 , 34 , 51 54 .…”
Section: Discussionmentioning
confidence: 99%
“…All the separations are carried out at ambient temperature. The gradient elution of solvent A (water-acetic acid) and solvent B (acetonitrile) had a significant effect on the resolution of compounds according to the procedure: 0 min, 100% (A); 5 min, 95% (A); 17 min, 85% (A); 40 min, 60% (A); 60 min, 50% (A); 65 min, 50% (A); 70 min, 100% (A) 33 , 34 .…”
Section: Methodsmentioning
confidence: 99%